Hemobilia. An unusual complication of liver trauma - Baeza Herrera Carlos; Toledo Sánchez Oliver Antelmo; Rodríguez Pulido Rubén (Instituto Nacional de Pediatría, 2014)
Introduction. Hemobilia is a complication following a hepatic trauma. It is common in adults, but it is very rare in children. Clinically it is characterized by a triad including jaundice, inter- mittent abdominal pain and gastrointestinal hemorrhage. Case report. We report a case of hemobilia in a four-year-old boy who sustained an abdominal blunt trauma caused by a motor vehicle. He had to be operated. A laparotomy disclosed a ruptured spleen which required a splenorraphy. He was subsequently discharged. Eighteen days later he was readmitted presenting with the classic triad. A computed tomography (CT scan) showed an image sug- gestive of hemobilia. Management was conservative. The child had an uneventful course.